The nerve protection and in vivo therapeutic effect of Acalypha indica extract in frogs (Medical Journal of Indonesia, 2010)
Aim To demonstrate nerve protection and/or treatment effect of Acalypha indica Linn. extract on nerve paralysisÂ induced by subcutaneus injection of pancuronium bromide on frog's back. Methods The study was performed on sixty frogs (Bufo melanostictus Schneider) that divided into two groups, i.e. the neuro-protection and neuro-therapy group. Each group was divided further into 6 sub-treatment groups: negative control group treated by water and positive control group treated by piracetam, treatment groups received the extracts 200, 300, 400, 500 mg/kgBW. Pancuronium bromide 0.2% (1 : 20 dilutions) were injected subcutaneously as muscle relaxant. The protective effect was studied by giving the extract orally, 1 hour prior to injection; while the therapeutic effect of the extract was studied by 10 minute treatment after injecting pancuronium bromide solution. The parameters measured were the onset and duration of paralysis (in minutes) and the recovery time (time needed to recover into normal condition). Results The study showed significantly different protective effect of Acalypha indica Linn. root water extract at 400 and 500 mg/KgBW compared to negative control group and positive control group (piracetam (p < 0.05); while the therapeutic effect was obvious at the dose 200-500 mg/KgBW compared to negative control group (p = 0.000). There was no significant difference compared to positive control group (piracetam), except at 300 mg/KgBW (p = 0.012). Conclusion These results have proven that the water extract of Acalypha indica Linn. root has comparable protective and treatment effect on nerves system, as piracetam, but further studies should be performed to provide more evidences particularly pharmacokinetic and pharmacodynamic studies on two animal models that commonly used. (Med J Indones 2010; 19:96-102)